Medication errors in intravenous drug preparation and administration: a multicentre audit in the UK, Germany and France - Cousins, D (BMJ Group, 2005)
Background: Previous studies have identified medication errors in preparing and administering intravenous medicines of 13–84% in hospitals in individual countries. Objective: To compare the effect of the design and implementation of systems for the preparation and administration of intravenous therapy in hospitals in three European countries on the number of observed medication errors. To gain a better understanding of these risks and the methods used in each country to manage them. Design: Prospective audit. Setting: Six hospital departments in the UK, Germany and France willing to participate in the audit as part of a quality improvement programme. Methods: Direct observation of the preparation and the administration of intravenous drugs made by a single observer in each country. Main outcome measures: Medication process errors. Results: 824 doses were prepared and 798 doses administered. The product was either not labelled or incorrectly labelled in 43%, 99%, and 20% of doses administered in the UK, German and French hospitals, respectively. The wrong diluent was used in 1%, 49% and 18% of cases, respectively, and the wrong rate of administration was selected for 49%, 21% and 5% of doses observed, respectively. At least one deviation from aseptic technique was observed among 100%, 58%, and 19% of cases in the three countries. Conclusion: Uncontrolled risks in the intravenous systems studied were observed in all three countries. Intravenous therapy must be regarded as a high risk activity where the use of risk management procedures to minimise risk to patients is seen as a high priority by all those involved with these duties. There is a requirement to develop better national (possibly international) procedures for safe intravenous practice.